Médecins, hôpitaux et poursuites judiciaires - Douville, Gérard R. (Assurances, 1984)
The author looks at patient's psychology in Quebec hospitals. There was a time when it was rare for a physician to be sued, and even rarer for action to be taken against a hospital. Mr. Douville believes that claims by dissatisfied patients will be more and more common, both against the doctors and the hospitals, and possibly against both together. He considers the situation in England, France and the U.S.A., and concludes that we will not be able to avoid for long the tendancy of certain people to claim, unless they have been convinced that the best knowledge and methods were used. We have already had several articles on the question of liability itself. This time, we have the view of a hospital manager who sees, in his hospital and in others, the gradual rise of claims for indemnity, both justified and unjustified.